Solvability for a New Class of Moore-Gibson-Thompson Equation with Viscoelastic Memory, Source Terms, and Integral Condition. (20th April 2021) - Boulaaras, Salah Mahmoud; Choucha, Abdelbaki; Ouchenane, Djamel; Alharbi, Asma; Abdalla, Mohamed; Cherif, Bahri Belkacem
Abstract : This paper deals with the existence and uniqueness of solutions of a new class of Moore-Gibson-Thompson equation with respect to the nonlocal mixed boundary value problem, source term, and nonnegative memory kernel. Galerkin's method was the main used tool for proving our result. This work is a generalization of recent homogenous work.